Astrocytes regulate vascular endothelial responses to simulated deep space radiation in a human organ-on-a-chip model - Verma, Sonali D.; Passerat de la Chapelle, Estrella; Malkani, Sherina; Juran, Cassandra M.; Boyko, Valery; Costes, Sylvain V.; Cekanaviciute, Egle (Frontiers in Immunology, 2022)
Central nervous system (CNS) damage by galactic cosmic ray radiation is a major health risk for human deep space exploration. Simulated galactic cosmic rays or their components, especially high Z-high energy particles such as 56Fe ions, cause neurodegeneration and neuroinflammation in rodent models. CNS damage can be partially mediated by the blood-brain barrier, which regulates systemic interactions between CNS and the rest of the body. Astrocytes are major cellular regulators of blood-brain barrier permeability that also modulate neuroinflammation and neuronal health. However, astrocyte roles in regulating CNS and blood-brain barrier responses to space radiation remain little understood, especially in human tissue analogs. In this work, we used a novel high-throughput human organ-on-a-chip system to evaluate blood-brain barrier impairments and astrocyte functions 1-7 days after exposure to 600 MeV/n 56Fe particles and simplified simulated galactic cosmic rays. We show that simulated deep space radiation causes vascular permeability, oxidative stress, inflammation and delayed astrocyte activation in a pattern resembling CNS responses to brain injury. Furthermore, our results indicate that astrocytes have a dual role in regulating radiation responses: they exacerbate blood-brain barrier permeability acutely after irradiation, followed by switching to a more protective phenotype by reducing oxidative stress and pro-inflammatory cytokine and chemokine secretion during the subacute stage.